Physiological aspects of fruit ripening: The mitochondrial connection - Perotti, Valeria Elisa (2014)
Fruit ripening is a genetically programmed process which leads to an assortment of physiological and metabolic changes that irreversibly alter its characteristics. Depending on the species, fruit maturation can be either climacteric or non-climacteric. In both cases there is a metabolic shift from normal development conditions toward the fully mature state, but climacteric fruit is characterized by a sharp increase in respiration. In non-climacteric fruit, that generally does not display this feature, respiration changes can be affected by processes related to postharvest storage. This review describes some of the many ways in which mitochondrial metabolism is implicated in this crucial reproductive stage, such as the connection between ethylene production and respiration rate, the involvement of alternative oxidase (AOX) and plant uncoupling mitochondrial protein (PUMP) during the ripening and the common alterations of this organelle in fruits affected by different stress conditions